Unusual Long-Term Survival in an Adult Patient With Langerhans Cell Histiocytosis and Central Nervous System Involvement: A Case Report - María José Miranda Pallarés; Tomás Álvaro Naranjo; Anna Vidal Rodriguez; Francisca Martínez Madueño (Case Reports in Hematology)
Langerhans cell histiocytosis (LCH) in adults is a rare condition. The disease presents with focal or multifocal involvement of a single organ/system or focal or disseminated multisystem disease. Involvement of the central nervous system (CNS) is also infrequent, with diabetes insipidus as a common manifestation of posterior pituitary lesions. Biopsy-proven diagnosis with the observation of characteristic Langerhans cells infiltrate with positive immunohistochemistry of S100 protein, CD1a, and CD68 cells. The patient presented generalized lymphadenopathy and was diagnosed with low-risk single-system LCH-based distinctive pathological findings in a lymph node biopsy. During the disease, CNS involvement was documented and the patient received different sequential therapeutic schemes, achieving complete remission that has been maintained for 8 years. The prolonged duration of remission with disappearance of lymphadenopathy and CNS lesions in an adult patient with LCH is an unusual clinical observation.